Insect-based chitin and chitosan from whole body sources and rearing by-products: Extraction, physicochemical, structural and bioactivity characterisation - Navarro, P. (2025)
Fractionation of edible insects and their rearing by-products can lead to expanded industrial applications and extraction of value-added products. The main goal of this study was to extract chitin and synthesise chitosan from three different insect sources ‒ Tenebrio molitor larvae, adult Acheta domesticus and A. domesticus rearing by-products (legs and wings). Furthermore, the physicochemical, structural, and bioactive properties of insect-derived chitin and chitosan were characterised and compared to commercial crustacean-based samples. Chitin was isolated from defatted sources through chemical hydrolysis followed by decolourisation and was deacetylated with a strong alkaline solution to synthesise chitosan. Notably, A. domesticus rearing by-products yielded the highest chitin and chitosan content. Chitin and chitosan derived from insects exhibited physicochemical and structural characteristics consistent with the α-polymorphic form, similar to the commercial samples. Differences were found in surface morphology, with insect-derived samples presenting large and irregular flakes and porosity, while the crustacean-derived samples presented irregularly arranged fibres and a more regular and smoother surface. As for antioxidant activity, although all chitosan samples demonstrated poor DPPH radical scavenging activity, this study showed for the first time that insect-derived chitosan presents lipid peroxidation inhibition ability. All chitosan samples presented antimicrobial activity against different pathogenic bacteria, with K. pneumoniae being the most susceptible strain. Nevertheless, there is potential for enhancement of the biological properties through modifications on the molecular weight and deacetylation degree. This research introduces the potential of cricket-rearing by-products as sustainable sources of chitosan with functional bioactive properties.